(untitled) (Journal of actual problems of jurisprudence, 2018)
Nikolai Alexeyev, the great lawyer and the founder of the Eurasian concept. The core of the Eurasian idea with the assistance of the European priorities scientist believes that it is necessary to determine the psychology of the people living in the area. Find a middle ground between the East and West, a scientist has an important place in the works. Eurasian region as a result of the process, which lasted many centuries ethnic area to create a flexible state and legal system. Supports the idea of a scientist working on the development of the regional peculiarities of the country. Key words: Eurasianism, state, law, mission.